2019 IEEE Frontiers in Education Conference (FIE) 2019
DOI: 10.1109/fie43999.2019.9028475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of Remixing in Scratch Projects Based on Repertoire, Lines of Code (LOC), and Elementary Patterns

Abstract: This Full Paper in the Research Category evaluates the use of remixing in Scratch. A feature of the Scratch programming environment is that it supports students to share their code and "remix" (modify) other students' code. Remixing in Scratch has garnered much attention by the research community as use of collaboration for learning was one of the main ideas behind Scratch. It can provide opportunities to read others' code, learn how features can be implemented using the Scratch language, and contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…However, we have observed that often the modifications are not around learning programming (such as changing a backdrop or sprite), and in some cases almost no modification is made at all [20]. Since, we are working with all projects for each user in our sample, the remixed projects will not have a big impact on the results reported here as the remixing percentage is usually between 0-25% [21].…”
Section: Analysis Evaluation and Resultsmentioning
confidence: 93%
“…However, we have observed that often the modifications are not around learning programming (such as changing a backdrop or sprite), and in some cases almost no modification is made at all [20]. Since, we are working with all projects for each user in our sample, the remixed projects will not have a big impact on the results reported here as the remixing percentage is usually between 0-25% [21].…”
Section: Analysis Evaluation and Resultsmentioning
confidence: 93%
“…Cada participante pode se inspirar na atividade da oficina que mais gostou para construir um novo programa, a ser apresentado para os colegas e as monitoras no último encontro. Como cada participante pode definir o tema e as funcionalidades, espera-se que a complexidade do código produzido reflita, de alguma forma, o entendimento dos conteúdos apresentados e a segurança do participante em modificar (ou remixar [1,9]) o código com o qual já teve contato prévio. Considerando, ainda, que não é esperada a produção de código muito complexo, optou-se por fazer uma contagem simples da quantidade de estruturas de programação presentes no código dos participantes em cada uma das categorias: blocos de movimentação; estruturas condicionais, de repetição e eventos; definição e uso de variáveis, impressão de frases na tela, impressão e modificação de sprites, e modificação visual, que engloba comandos relacionados a definição de cores, tamanhos e trajes de sprites, planos de fundo, adesivos e largura de traços.…”
Section: Análise Do Código Produzido Pelos Participantesunclassified
“…A large portion of Scratch projects are remixed projects [28], but as many projects are relatively complex to remix [22], remixers may not always learn from reuse. Amanullah and Bell found that remixers rarely understand the original program, and rarely transfer concepts from the remixed program to their own future programs [2]. Khawas et al also found that the remixers rarely used cloning correctly or included new procedures [22].…”
Section: Related Workmentioning
confidence: 99%